Perceptions of doctors and nurses at a Ugandan hospital regarding the introduction and use of the South African Triage Scale - Francis Mulindwa; Julia Blitz (AOSIS, 2016)
Background: International Hospital Kampala (IHK) experienced a challenge with how to standardise the triaging and sorting of patients. There was no triage tool to help to prioritise which patients to attend to first, with very sick patient often being missed. Aim and setting: To explore whether the introduction of the South African Triage Scale (SATS) was seen as valuable and sustainable by the IHK's outpatient department and emergency unit (OPD and EU) staff. Methods: The study used qualitative methods to introduce SATS in the OPD and EU at IHK and to obtain the perceptions of doctors and nurses who had used it for 3-6 months on its applicability and sustainability. Specific questions about challenges faced prior to its introduction, strengths and weaknesses of the triage tool, the impact it had on staff practices, and their recommendations on the continued use of the tool were asked. In-depth interviews were conducted with 4 doctors and 12 nurses. Results: SATS was found to be necessary, applicable and recommended for use in the IHK setting. It improved the sorting of patients, as well as nurse-patient and nurse-doctor communication.The IHK OPD & EU staff attained new skills, with nurses becoming more involved in-patient care. It is possibly also useful in telephone triaging and planning of hospital staffing. Conclusion: Adequate nurse staffing, a computer application for automated coding of patients, and regular training would encourage consistent use and sustainability of SATS. Setting up a hospital committee to review signs and symptoms would increase acceptability and sustainability. SATS is valuable in the IHK setting because it improved overall efficiency of triaging and care, with significantly more strengths than weaknesses. Keywords: South African Triage Scale; Perceptions